Germination and fungal infection of wild celery (Apium graveolens L.) seeds, from southern Brazil, under different temperature and disinfection conditions - Brum Doncato, Kennia; Serra Bonifácio Costa, César (Revista Ceres, 2025)
Seeds of wild celery (Apium graveolens L.) from southern Brazil were surface disinfected with different solutions of sodium hypochlorite (5 and 10%) and acetic acid (0.5, 1, 2, 4%), and germination success and fungal infection were evaluated after 28 days of incubation at a constant temperature of 30 ºC and 20/30 ºC thermoperiod (12h:12h). Germination of wild celery was inhibited at the constant temperature (30 ºC). Vigorous total germination (90–100%), a faster germination velocity (1.8–2.5 germinated seeds per day) and moderate fungal infection (53.3–81.7%) of wild celery seeds were obtained with the sodium hypochlorite treatments (5–10% concentration) under the 20/30 ºC thermoperiod. The 4% treatment of acetic acid was very effective at preventing seed fungal infection (only 5% of the seeds) but it reduced theaverage total germination to 60%. Lower concentrations of acetic acid (0.5–2%) resulted in 100% fungal infection. In conclusion, seedlings of wild celery from southern Brazil can be effectively produced by disinfecting the seeds with 5-–10% sodium hypochlorite and incubation under a 20/30 ºC thermoperiod (12h:12h).